2019
DOI: 10.1161/circulationaha.119.040629
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypically Silent Bone Morphogenetic Protein Receptor 2 Mutations Predispose Rats to Inflammation-Induced Pulmonary Arterial Hypertension by Enhancing the Risk for Neointimal Transformation

Abstract: Background: Bmpr2 (bone morphogenetic protein receptor 2) mutations are critical risk factors for hereditary pulmonary arterial hypertension (PAH) with approximately 20% of carriers developing disease. There is an unmet medical need to understand how environmental factors, such as inflammation, render Bmpr2 mutants susceptible to PAH. Overexpressing 5-LO (5-lipoxygenase) provokes lung inflammation and transient PAH in Bmpr2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 49 publications
2
60
0
Order By: Relevance
“… 41 Although valuable as preclinical research tools, these models do not reproduce the near-complete BMPR-II deficiency that is observed in many patients with PAH. Future studies exploring the impact of BMP9 administration on the pathophysiology of PAH in the Bmpr2 EC −/− conditional knockout, either at baseline or in response to PAH-inducing stimuli like chronic hypoxia or 5-lipoxygenase overexpression, 42 , 43 will help to establish the functional relevance of our current findings to this subset of BMPR2 -deficient PAH patients.…”
Section: Discussionmentioning
confidence: 85%
“… 41 Although valuable as preclinical research tools, these models do not reproduce the near-complete BMPR-II deficiency that is observed in many patients with PAH. Future studies exploring the impact of BMP9 administration on the pathophysiology of PAH in the Bmpr2 EC −/− conditional knockout, either at baseline or in response to PAH-inducing stimuli like chronic hypoxia or 5-lipoxygenase overexpression, 42 , 43 will help to establish the functional relevance of our current findings to this subset of BMPR2 -deficient PAH patients.…”
Section: Discussionmentioning
confidence: 85%
“…A two-hit model is also proposed in hereditary pulmonary arterial hypertension (hPAH), in which Bmpr2 mutations is a strong susceptibility factor but where only 20% of carriers develop the disease. Pulmonary inflammation, generated by overexpressing 5-lipoxygenase (a condition observed in hPAH patients), was associated with severe PAH in Bmpr2 +/− rats, while neither the single ‘hit’ of Bmpr2 haploinsufficiency nor 5-LO-specific pulmonary inflammation alone initiated the disease—their combined presence was required to develop a lethal PAH [200].…”
Section: Discussionmentioning
confidence: 99%
“…In spite of this trial failing to reach its primary endpoint, promising preclinical studies still implicate LTB4 in PAH pathogenesis in specific subpopulations. A recent study demonstrated that in BMPR2 haploinsufficient rats, the viral transduction of 5-lipoxygenase (5-LO), the enzyme that produces LTB4, results in the development of severe PAH [ 56 ]. Of note, BMPR2 mutations are among the most common human mutations found in hereditary PAH, albeit with low penetrance [ 57 ].…”
Section: Inflammatory Mediators and Their Effects On Vascular Remomentioning
confidence: 99%
“…The transduction of 5-LO resulted in the development of PAH in these rats with similar frequency to humans with BMPR2 mutations. Additionally, the neointimal cells in these animals developed a spontaneous, endogenous expression of non-viral 5-LO, which is a finding that was also seen in patient tissue [ 56 ]. Together, these data demonstrate a fundamental interplay between leukotrienes, transforming growth factor (TGF)-β / bone morphogenic protein (BMP) signaling, and the development of PAH.…”
Section: Inflammatory Mediators and Their Effects On Vascular Remomentioning
confidence: 99%